Idioma ingles y su influencia en el ámbito profesional de las secretarias ejecutivas en la Empresa Torres y Torres en el año 2022 - Manzaba Mindiola, Maybeli Jomely (2022)
This case study is called the English Language and It’s Influence in the Professional Environment of the Executive Secretaries in the Torres y Torres Company. Where we can observe the abilities and shortcomings that the secretaries present in the language and how it entails it in the professional field and in their daily activities, in relation to the needs of the secretarial department of the Torres y Torres company, the environment where the present investigation is carried out; as a general objective, "Analyze the relationship of the English Language in the professional field of the Executive Secretaries in the Torres y Torres company." The explanatory and descriptive method was used because they are better to define and achieve the stated objectives that are planned to be obtained from the executive secretaries, in addition to knowing what percentage they have of knowledge of the English language in order to improve the professional field. The instrument we used to collect information was the interview: the same one that was carried out with the secretaries of the Torres y Torres company to evaluate job performance, the different activities, and the use of the English language through the exchange of sales and attention with the clients. The same was applied through a questionnaire of eight questions developed based on the two variables of the research topic. A secretarial staff of five people involved in the problem was also considered, evidencing the development in this document.